Contrasting activity patterns at high and low tide in two Brazilian fiddler crabs (Decapoda: Brachyura: Ocypodidae) - De Grande, Fernando R. [UNESP]; Colpo, Karine D.; Queiroga, Henrique; Cannicci, Stefano; Costa, Tania M. [UNESP] (Oxford Univ Press, 2018)
Fiddler crabs are known as ecosystem engineers as well as important connectors of energy flow between the intertidal zone and the adjacent marine and terrestrial environments, being predated by both marine and terrestrial species. Studies on their activity patterns are critical to understand their overall role in the function of estuarine ecosystems. Recent studies have found that fiddler crabs, which are active at low tide, are the main food item of fishes hunting at high tide in the intertidal zone, suggesting that some species could also be active at high tide. We assessed the activity patterns of two fiddler crabs, Leptuca leptodactyla (Rathbun, 1898) and L. thayeri (Rathbun, 1900) using pitfall traps deployed at different diurnal and tidal conditions at two southeast Brazilian estuaries. Our data shows that L. leptodactyla was mostly active at low tide during both day and night, whereas L. thayeri was active at low and high tide, a behavior uncommonly reported for fiddler crabs. Our results also confirm that some fiddler crabs can have a previously unreported importance as food for aquatic predators.
Keywords: fish predation; Leptuca leptodactyla; Leptuca thayeri; underwater activity